The Determinants of Work Motivation on Enhancing Employee Productivity at PT. Happy Path in Makassar - Rasyid, Muh Nur; Jusriadi, Edi; Hakib, Andi; Afrian, Muh Fuad (Universitas Muhammadiyah Makassar, 2025)
This study empirically examines the impact of work motivation on employee productivity and assesses its implications for human resource management strategies at PT. Happy Path, Makassar. Employee productivity is a crucial determinant of organizational success, and motivation is widely recognized as a key driver of performance. This quantitative study collected primary data from 120 employees selected through stratified random sampling. Data were analyzed using multiple linear regression and t-tests to determine the statistical significance of the relationship. The findings indicate that work motivation has a significant positive effect on employee productivity (β = 0.45, R² = 0.38, p < 0.05), explaining 38% of the variance in productivity levels. These results highlight the importance of motivation-enhancing strategies, such as performance-based incentives, career development programs, and a supportive work environment, in improving workforce efficiency. For PT. Happy Path, investing in well-structured motivational initiatives can be an effective approach to increasing employee performance and achieving organizational objectives. Future research should explore additional factors, including leadership style, job autonomy, and organizational culture, to gain a deeper understanding of the dynamics influencing employee productivity.